A Graph Based Approach to Identify Objects using Identifying Attribute - Anita Kushwaha; R.S. Pandey (Institute of Advanced Engineering and Science, 2017)
We have proposed a method to identify objects in database schema using association degree with other objects. We have also used identifying attribute of associations in graph to specify a unique path to resolve ambiguity of Fuzzy Object Functional Dependencies. Recently Fuzzy Concepts were used in Object Oriented Data Models. The Object Identifier allows distinguishing between similar objects. Functional Dependencies play a dominant role to uniquely identify objects. Moreover object identification has now become a modeling concept rather than database concept so starting a search for objects with a set of values is possible. We have also investigated the presence of identifying attributes in fuzzy object schema and its implications.